Sosialisasi Perlindungan Hukum terhadap Petani atas Ketersediaan Lahan Pertanian di Indonesia serta Sebagai Wujud Menciptakan Ketahanan Pangan Daerah - Imanudin Affandi; Devi Siti Hamzah Marpaung (Jurnal Pengabdian Nasional (JPN) Indonesia, 2023)
Issues of legal protection for farmers, food security and availability of farmland have strategic social, economic, and religious functions for Indonesian agricultural society. The unpredictability of land-use change threatens the resilience, independence and food sovereignty of farmers and communities. Therefore, government policy to protect sustainable farmland will continue to explore whether legal protections are needed for existing farmland as well as farmers to become permanent farmland. The purpose of this activity is to make farmers understand that they have the right to live a decent and prosperous life through the availability of the land itself, and the method is the preparation stage, the implementation stage, and the reporting stage. consists of During the implementation phase, non-profit activities such as demonstrations of socialization techniques, tree planting, and production of organic pesticide fertilizers were carried out. Socialization occurs through the engagement of performance goal partners and actively and interactively between resource personnel and participants. The official stressed that the availability of agricultural land is a fulfillment of rights that communities and the state must acquire, in which case local governments have an obligation to make efforts. The demonstration introduced the technology of producing organic pesticide fertilizers to increase the fertility of agricultural land in community service areas. This inaugural event went according to plan.